Church, State, Vellum, and Stone
1 online resource.
Keywords: The sixteen essays in this volume were written to honor John Williams's contributions to the study of medieval Spanish art and architecture. Contributors from the fields of Art History, History, and Archaeology were chosen to demonstrate Williams's wide-ranging influence as scholar and teacher. Thus, the collection represents current research by scholars from five countries, providing an interdisciplinary, international, and even intergenerational view of the work being done in Spanish medieval History and Art History today. With contributions by Achim Arbeiter, Simon Barton, Ann Boylan, James D'Emilio, Angela Franco, Julie A. Harris, Peter K. Klein, Therese Martin, Eileen P. McKiernan González, Pamela Patton, David Raizman, Bernard F. Reilly, Diane Reilly, Rocío Sánchez Ameijeiras, José Luis Senra, and Kenneth B. Wolf.